Communicating professionally : - Ross, Catherine Sheldrick (Neal-Schuman, an imprint of the American Library Association, 2013)
This updated and expanded version of the training guide Booklist called "one of the most valuable professional publications to come off the presses in a long time" is completely revised with new sections outlining the opportunities offered by contemporary communication media. This third edition incorporates updated and expanded references with more resource information on cross-cultural communication, including new applications of communication principles and the latest research-based material on communication in general.